2016
DOI: 10.1016/j.jfa.2016.04.011
|View full text |Cite
|
Sign up to set email alerts
|

On measuring unboundedness of the H∞-calculus for generators of analytic semigroups

Abstract: We investigate the boundedness of the H ∞ -calculus by estimating the bound b(ε) of the mapping H ∞ → B(X): f → f (A)T (ε) for ε near zero. Here, −A generates the analytic semigroup T and H ∞ is the space of bounded analytic functions on a domain strictly containing the spectrum of A. We show that b(ε) = O(| log ε|) in general, whereas b(ε) = O(1) for bounded calculi. This generalizes a result by Vitse and complements work by Haase and Rozendaal for non-analytic semigroups. We discuss the sharpness of our boun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 33 publications
(122 reference statements)
1
23
0
Order By: Relevance
“…The following corollary covers some ideas which are included in [78, Theorem 5.5.12, etc] using Peller's method, and in [44] 4), and a similar result for bounded holomorphic semigroups on Banach spaces was given by Schwenninger [67]. The results are immediate consequences of Lemma 3.2(2).…”
Section: 1mentioning
confidence: 60%
“…The following corollary covers some ideas which are included in [78, Theorem 5.5.12, etc] using Peller's method, and in [44] 4), and a similar result for bounded holomorphic semigroups on Banach spaces was given by Schwenninger [67]. The results are immediate consequences of Lemma 3.2(2).…”
Section: 1mentioning
confidence: 60%
“…Indeed, such an example can be constructed for an L 2 -space on the unit circle with suitable weight, see [26,Thm. 5.2], [42], and [44,Section 4.3]. In fact, the example in [42,Thm.…”
Section: Sharpness Of the Estimatesmentioning
confidence: 99%
“…A careful study of this sketch reveals that it is based on a similar approach as in Bakaev's proof, which, with a sharper estimation and some additional work, actually yields (1.6). We will encounter a similar approach in the proof of Theorem 2.3, which was actually motivated by a result of the author for analytic semigroups, [42].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the techniques here and in Vitse's work [15] require that the functions f are bounded, analytic on a half-plane. In [13] it is shown that the corresponding result is even true for functions f that are only bounded, analytic on sectors which are larger than the sectorality sector of the generator A.…”
Section: Closing Remarksmentioning
confidence: 98%